2000
DOI: 10.1046/j.1365-2141.2000.02107.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of the CD8+CD57+ cell population in normal healthy individuals and matched unrelated T‐cell‐depleted bone marrow transplant recipients

Abstract: Summary. The biological activities of CD81 that co-express CD57 remain poorly defined. It is unclear whether all CD8 1 cells have the potential to become CD57 1 or whether they represent a unique subset with distinct functions. Several studies have reported the association between elevated numbers of CD81 CD57 1 and a wide range of clinical disorders such as viral reactivation of human cytomegalovirus (HCMV). In this study, we have investigated the relationship between viral reactivation and the effect of dimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 12 publications
1
22
0
Order By: Relevance
“…We found rapid normalization or even overexpression of activated CD8 þ cells expressing CD57 or HLA-DR in the first months post transplantation. Early CD8 þ T-cell restoration led to a reversed CD4/CD8 ratio after RIC-PBSCT and may result from an initial expansion of transferred or residual CD8 þ T cells, as described by Rowbottom et al 35 Biological activity of CD8 þ /CD57 þ cells is unclear, but is supposed to contain anti-CMV cytotoxic T cells. 35,36 CD8 High /CD57 þ T cells arise from peripheral expansion and contribute to the oligoclonal antigen-dependent repertoire, while CD8 Low /CD57 þ are corresponding to NK cells, a cell subset also rapidly reconstituted in our study as usually observed after HSCT.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…We found rapid normalization or even overexpression of activated CD8 þ cells expressing CD57 or HLA-DR in the first months post transplantation. Early CD8 þ T-cell restoration led to a reversed CD4/CD8 ratio after RIC-PBSCT and may result from an initial expansion of transferred or residual CD8 þ T cells, as described by Rowbottom et al 35 Biological activity of CD8 þ /CD57 þ cells is unclear, but is supposed to contain anti-CMV cytotoxic T cells. 35,36 CD8 High /CD57 þ T cells arise from peripheral expansion and contribute to the oligoclonal antigen-dependent repertoire, while CD8 Low /CD57 þ are corresponding to NK cells, a cell subset also rapidly reconstituted in our study as usually observed after HSCT.…”
Section: Discussionmentioning
confidence: 80%
“…Early CD8 þ T-cell restoration led to a reversed CD4/CD8 ratio after RIC-PBSCT and may result from an initial expansion of transferred or residual CD8 þ T cells, as described by Rowbottom et al 35 Biological activity of CD8 þ /CD57 þ cells is unclear, but is supposed to contain anti-CMV cytotoxic T cells. 35,36 CD8 High /CD57 þ T cells arise from peripheral expansion and contribute to the oligoclonal antigen-dependent repertoire, while CD8 Low /CD57 þ are corresponding to NK cells, a cell subset also rapidly reconstituted in our study as usually observed after HSCT. 27 In agreement with previous studies, 20,37,38 we observed rapid NK cell reconstitution, since the median CD3À CD56 þ cell counts were close to the normal values as soon as M þ 1.5.…”
Section: Discussionmentioning
confidence: 80%
“…þ T cells were obtained by positive selection from mononuclear cells of human peripheral blood as previously described [21,22]. The purity of CD8 þ cells was assessed by flow cytometry and was routinely more than 98% (data not shown).…”
Section: Cd8mentioning
confidence: 99%
“…Samples of fresh (preculture) and cultured CD8 þ cells were stained using fluorescent-labelled monoclonal antibodies CD45RA, CD45RO, CD8 and CD57 to confirm their immunophenotype. All antibody staining steps were performed at 4 C for 30 min as described previously [21,22]. Appropriate isotype controls were also performed for each marker.…”
Section: Cd8mentioning
confidence: 99%
See 1 more Smart Citation